The application of neural networks and min-max algorithm in digital congkak - Che Pa, Noraziah; Alwi, Asmidah; Mohamed Din, Aniza; Safwan, Muhammad (2013)
To date, there are lots of intentions and efforts made to attract young generations with cultural games by promoting, preserving and cultivating cultural games using myriad mediums such as books, e-books, blogs, social media and portals. Supporting the efforts, this paper presents works of digitizing one of Malaysian traditional games, namely Congkak. A digital Congkak was developed based on Mancala, African traditional game which is similar to Congkak. To make it intelligent, its player agent was developed using a combination of Neural Networks and Min-Max algorithm. Methods, findings and evaluation of the digitized Congkak are presented and discussed.